Polyphosphates form antigenic complexes with platelet factor 4 (PF4) and enhance PF4-binding to bacteria - Brandt, Sven; Krauel, Krystin; Jaax, Miriam; Renné, Thomas; Helm, Christiane A.; Hammerschmidt, Sven; Delcea, Mihaela; Greinacher, Andreas (Thrombosis and Haemostasis, 2015)
Short chain polyphosphates (polyP) are pro-coagulant and pro-inflammatory platelet released inorganic polymers. The platelet chemokine platelet factor 4 (PF4) binds to lipid A on bacteria, inducing an antibody mediated host defense mechanism, which can be misdirected against PF4/heparin complexes leading to the adverse drug reaction heparin-induced thrombocytopenia (HIT). Here, we demonstrate that PF4 complex formation with soluble short chain polyP contributes to host defense mechanisms. Circular dichroism spectroscopy and isothermal titration calorimetry revealed that PF4 changed its structure upon binding to polyP in a similar way as seen in PF4/heparin complexes. Consequently, PF4/polyP complexes exposed neoepitopes to which human anti-PF4/heparin antibodies bound. PolyP enhanced binding of PF4 to Escherichia coli, hereby facilitating bacterial opsonisation and, in the presence of human anti-PF4/polyanion antibodies, phagocytosis. Our study indicates a role of polyP in enhancing PF4-mediated defense mechanisms of innate immunity.
Keywords: Antigen generation; conformational changes; phagocytosis; platelet factor 4; polyphosphates